Correspondencia estructural para la copula en Anthidium (Hymenoptera: Megachilidae) - Toro, H.=700 1 Rodriguez, S.
(Es, En)
Ilus., 18 ref.
Keywords: HYMENOPTERA; FUNCION FISIOLOGICA; COPULA; CHILE; APOIDEA; ANTHIDIUM; REVISTA CHILENA DE ENTOMOLOGIA